Tuberculous osteomyelitis affecting periodontium: A rare case report - Gaurav Bakutra; Balaji Manohar; Lalit Mathur (Wolters Kluwer Medknow Publications, 2015)
Tuberculous lesions affecting periodontium are rare and seen as secondary infections localized to the soft tissues. With the advent of effective drug therapy, tuberculous lesions of the oral cavity have become rare. Involvement of the periodontium has seldomly been reported in the recent literature. We report a case of tuberculous osteomyelitis of mandible affecting periodontium leading to gingival recession and bone exposure in the mandibular premolar region in a 42-year-old female patient. The diagnosis was based on patient's medical and dental history, bacterial culture, clinical and radiographic examination, blood investigation, immunologic tests, histopathologic examination of the tissue specimen. Patient was already taking antitubercular chemotherapy prescribed by physician. Sequestrectomy and decortications were carried out to remove the affected bone. Healing was uneventful and there was no recurrence after 1½ year of follow-up. Antitubercular chemotherapy along with sequestrectomy and decortication are the treatment of choice for tuberculous osteomyelitic lesions affecting periodontium.